Hubungan Nafsu Makan pada Anak Balita dengan Kejadian Stunting di Wilayah Kerja Puskesmas Ahuhu - Al Dhamir, Muh Fitrah; Abadi, Ellyani; Demmalewa, Jenny Qlifianti (Sekolah Tinggi Ilmu Kesehatan Karya Kesehatan, 2024)
A major dietary issue that can impact a child's growth and development before the age of five is stunting. Appetite is one of the elements that affects the prevalence of stunting. The purpose of this study is to examine the connection between stunting rates in the Puskesmas Ahuhu working region and the appetite of children under five. This study employed a cross-sectional methodology and a descriptive correlational design. Seventy-two stunted toddlers, ages six to fifty-nine months, made up the research population. Purposive sampling was the method of sampling that was employed. Questionnaires and observation were used to gather data, which were subsequently subjected to univariate and bivariate analysis. The majority of toddlers with stunting had weak appetites, according to the research. Statistical analysis shows that there is a significant relationship between appetite and the incidence of stunting, where a good appetite contributes to reducing the risk of stunting. There is a significant relationship between appetite in children under five and the incidence of stunting. It is recommended that parents pay more attention to their children's diet and increase their appetite by providing nutritious and attractive food